Health related quality of life of dialysis patients in Malaysia: Haemodialysis versus continuous ambulatory peritoneal dialysis - Surendra, Naren Kumar (BMC Nephrol, 2019)
BACKGROUND: Health related quality of life (HRQOL) is an important predictor of clinical outcomes for End Stage Renal Disease (ESRD) patients and to establish quality adjusted life years (QALYs) for economic evaluation studies. This study aims to measure the health utilities and to identify socio-demographic and clinical factors associated with HRQOL for haemodialysis (HD) and continuous ambulatory peritoneal dialysis (CAPD) in Malaysia. METHODS: A total of 141 patients (77 HD and 64 CAPD) from 1 federal and four state hospitals participated in this cross-sectional study. Patients were randomly selected from the National Renal Registry (NRR) using a stratified random sampling. The EQ-5D-3 L questionnaire was used to measure HRQOL. Variables investigated include dialysis modalities, sociodemographic characteristics, co-morbidities and biochemical markers. Utilities are measured on an ordinal scale of 0–1, where 1 indicates full health and 0 indicates death. RESULTS: The mean utility scores were 0.854 ± 0.181 and 0.905 ± 0.124 (p > 0.05) and the mean Visual Analogue Scale (VAS) scores were 76.2 ± 12.90 and 77.1 ± 10.26 (p > 0.05) for HD and CAPD patients respectively. There was a significant difference in problems reported between HD (35.1%) and CAPD (15.6%) on usual activities dimension (p = 0.009). The proportion of patients having problems in the pain/discomfort domain in both modalities was high (34.0%). Haemoglobin (< 10 g/dL) (p = 0.003), number of co-morbidities ≥3 (p = 0.004) and wheelchair-bound status (p < 0.001) were significant predictors of poor HRQOL. CONCLUSIONS: The present cross-sectional study shows that CAPD patients have a higher utility index score than HD patients but this was not statistically significant. The utilities index score may be used to calculate QALYs.